Age and Sex Characteristics of Dermatophytosis in Gianyar, Indonesia - Budiapsari, Putu Indah; Purnama, Ni Kadek Ari; Widiawati, Sayu (Folia Medica Indonesiana, 2024)
Highlights: 1. Although dermatophytes may typically cause mild infections, it is crucial to conduct continuous research due to their potential to cause severe diseases in individuals who are highly susceptible to infection. 2. This study offers insight into the increased risk of developing dermatophytosis for female and adult individuals compared to male and younger individuals. Abstract Dermatophytosis is a superficial fungal infection caused by a filamentous fungus that attacks keratinized tissues on the skin, nails, and hair. The clinical manifestation of dermatophytosis is determined by the source. In addition, it can be influenced by host-related factors, such as age, sex, and race. These are significant epidemiological factors, although the association between these factors and susceptibility to infection has not been clarified. Therefore, this study aimed to determine the association between the incidence of dermatophytosis and host-related factors (i.e., age and sex) in Gianyar Regency, Indonesia. This observational study used a cross-sectional design and total sampling. A total of 100 samples were collected from the medical records of patients diagnosed with dermatophytosis. The Chi-square test was employed to determine the correlation between the independent and dependent variables with a p-value of <0.05. The data were analyzed using IBM SPSS Statistics for Windows, version 22.0 (IBM Corp., Armonk, N.Y., USA). The majority of patients with dermatophytes infection were adults over the age of 19 (74%) and females (57%). The most prevalent type of dermatophytosis was tinea corporis (36%). The Chi-square test revealed a significant association between the type of dermatophytosis and the variables being examined, namely age (p = 0.025; OR = 1.978; 95% CI = 1.087-3.599) and sex (p = 0.003; OR = 2.357; 95% CI = 1.334-4.162). In conclusion, the manifestation of certain types of dermatophytosis is associated with age and sex. The findings of this study recommend enhancing the detection of dermatophytosis infection, especially in adults (>19 years old) and women.